2018
DOI: 10.1371/journal.pone.0203151
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in Spanish women with breast cancer

Abstract: PurposeTo determine whether there are changes in sexuality after breast cancer, to better understand the sexual function of women with breast cancer, and to investigate the potential relationship between sexual dysfunction and socio-demographic and clinical variables.MethodsA cross-sectional study. This study included 514 women with breast cancer between 21- and 66-years-old. The cases were gathered between June 2016 and January 2017. The instruments used were the questionnaire on Women’s Sexual Function and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
1
26
0
4
Order By: Relevance
“…In this study, approximately half of the women had sexual dysfunction. Cobo-Cuenca et al and Abril-Requena et al also found similar results in a population of Spanish women with BC [26,27]. Sexual function is an important component of HRQoL among BC survivors.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, approximately half of the women had sexual dysfunction. Cobo-Cuenca et al and Abril-Requena et al also found similar results in a population of Spanish women with BC [26,27]. Sexual function is an important component of HRQoL among BC survivors.…”
Section: Discussionsupporting
confidence: 52%
“…Younger patients reported less sexual dysfunction because they still have functional ovaries. 11 Conversely, Harirchi, Montazeri 6 reported that younger breast cancer patients had FSD after breast cancer treatment. Young patients who underwent adjuvant therapy can develop premature menopause, which is associated with a poorer quality of life, lower sexual functioning, menopausal symptoms, and psychosocial distress related to infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide studies have reported that 31.6%–91.2% of breast cancer patients develop female sexual dysfunction (FSD) post-treatment. 5 , 6 , 7 , 8 , 9 , 10 , 11 Breast cancer patients face many difficult tasks along the way to restoring their sexual health after undergoing breast cancer treatment, including surgery. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Martins et al (2020) explica que as alterações mais presentes nesses casos são atrofias vulvovaginais, dispareunia, irritação e secura vaginal, inibição do desejo ou excitação, menopausa prematura, náuseas, vômitos e fadiga. Um estudo transversal espanhol publicado em 2018, tendo como amostra 514 mulheres, estudou a disfunção sexual em decorrência do câncer de mama, trazendo justificativas semelhantes, como dispareunia, falta de lubrificação, desejo e excitação sexual (Cobo-Cuenca et al, 2018).…”
Section: Categoria 2 -O Relacionamento Afetivo-sexualunclassified